1996
DOI: 10.1016/s0896-6273(00)80074-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective Adhesion of Cells from Different Telencephalic Regions

Abstract: We asked whether specifications of different regions of the rodent and avian telencephalon during development involved the acquisition of differential adhesive properties. Cells from different regions were aggregated in a short-term aggregation assay, and their segregation was analyzed. Both neurons and precursor cells from cortex segregate from striatal cells at early, but not later, stages, whereas cells from rodent neocortex and hippocampus segregated only during later stages. Segregation was abolished when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 75 publications
4
65
0
Order By: Relevance
“…To investigate the role of bidirectional ephrinB3-EphA4 signaling in the segregation of interneurons deriving from the two migratory routes after cell-cell contact, we performed a shortterm aggregation assay modified according to Gotz et al (1996). The initial aggregation of dissociated cells in this assay was described to reflect the expression and function of cell surface signaling molecules, restricting cellular mixing to maintain positional information during forebrain development (Gotz et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the role of bidirectional ephrinB3-EphA4 signaling in the segregation of interneurons deriving from the two migratory routes after cell-cell contact, we performed a shortterm aggregation assay modified according to Gotz et al (1996). The initial aggregation of dissociated cells in this assay was described to reflect the expression and function of cell surface signaling molecules, restricting cellular mixing to maintain positional information during forebrain development (Gotz et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…The aggregation assay was modified after Gotz et al (1996). In brief, dissociated cells of the VZ/SVZ and IMZ of the MGE of EGFP-expressing embryos and wild-type littermates were prepared as described above and collected in GBSS, which was then substituted by Ca 2ϩ /Mg 2ϩ -free HBSS with 1 mM EDTA (dissociation buffer).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pax6 mutant fails to establish the boundary between the cortical and striatal regions (6, 8, 14 -18). It has been proposed that Ca 2ϩ -dependent selective adhesion of the cortical cells segregating from the striatal cells contributes to the formation and maintenance of boundaries between these telencephalic regions (19). In Pax6 mutant, this selective adhesion of cortical cells is lost (16) and neural cell migration from the striatum into the cortex is strongly enhanced (20).…”
mentioning
confidence: 99%
“…It has been reported that the cortex of the rat telencephalon at embryonic days 12 to 15 (E12-15) 1 distinctively expresses Lewis x epitope (19,21,22). The Lewis x epitope, which is also known as CD15 and SSEA-1 (stage-specific embryonic antigen-1), has been identified as a glycan epitope with a Gal␤1-4(Fuc␣1-3)GlcNAc␤1-structure (23)(24)(25).…”
mentioning
confidence: 99%